Crustal Scale Imaging of the Arabia‐Central Iran Collision Boundary Across the Zagros Suture Zone, West of Iran. Issue 8 (19th April 2020) - Dashti, F.; Lucente, F. P.; Motaghi, K.; Bianchi, I.; Najafi, M.; Govoni, A.; Shabanian, E.
Abstract: We calculate seismic velocity structure of the north Zagros suture zone, west Iran, to resolve the crustal features at the boundary of Arabian‐Central Iranian collision. We compute teleseismic receiver functions (RFs) for 46 stations along a transect crossing the suture. Through harmonic analysis and inversion of the RF data, we obtain information on the characteristics of the suture zone at depth. The RFs and their harmonics show a low angle NE dipping boundary between the overriding layer and a midcrustal low velocity zone, which corresponds to the suture zone. The overriding high velocity feature (Vs ~ 3.8 km/s) is interpreted as an intermediate depth crustal complex exhumed close to the surface through imbricate thrust faulting and enhanced by crustal buoyancy due to continental underthrusting. Significant anisotropy is found above and below the suture zone: We interpret it in terms of slow‐symmetry‐axis anisotropy and derive clues on the ongoing deformation processes. Key Points: We confirmed existence of a weak shear zone in the suture between Arabian plate and the Eurasia in western Zagros Overriding crust exhumed close to the surface through imbricate thrust faulting and enhanced by crustal buoyancy Rock foliation and fluid or melt filled fractures formed during the shearing are potential source of anisotropy in both side of the suture